A low-cost digital torquemeter coordinated by arduino board - Ashwindran, S. N.; Azizuddin, Abd Aziz; Oumer, A. N. (Penerbit UTHM, 2023)
Torquemeter is a transducer for measuring rotational force and converting it into electronic output signal. In this paper, the techniques to fabricate a low cost yet effective torquemeter system is introduced. The device is calibrated and tested to prove it effectiveness and robustness. The system is developed to investigate the torque generated by wind turbine system. The presented torquemeter system comprises of two subsystems namely photointerrupter (primary) and load cell (secondary). The reliability of the developed system is analyzed by stages in order to verify the effectiveness in acquiring measurement namely RPM, weight (load) and torque. It is found that 5 kg load cell illustrated unsteady noise behavior relative to the defined calibration weight. Meanwhile, the percentage of accuracy (Pa) of final 3th reading is Pa = 94.709 %, 97.32 %, 98.826 % for 10 g, 20 g and 100 g respectively. Measurement acquired from torquemeter system is compared against 2D CFD numerical model under similar flow condition. Results shows that the measurement of torquemeter system is Mt = 0.731842 and as for CFD model is Mt = 0.82553 which results in error (%) of Pe = 11.35 %. However, the CFD numerical model has overpredicted moment value since it has compensated the blockage factor and external environmental factors. It is safe to say, that the presented instrument is applicable and feasible for WT torque acquisition